Mediemad, køn og et ruralt etos : Inklusion af agrikulturelle færdigheder i mediemadens køns-forhandlinger - Ostrowski, Kasper; Gunder Strøm Krogager , Stinne (STS Encounters, 2016)
Through cross-media exemplification this article investigates how a rural ethos and agricultural proficiencies seem included in contemporary media food and how this challenge clear-cut gender distinctions by changing the centre of attention from gendered consumption and preparation of food to a less clearly demarcated domain of food production. In the increasingly popular media foodscape, gender stereotypes are continuously orchestrated clearly as either feminine or masculine: The feminine media food is domestic, light, easy and characterized by healthy, modest and quick ferial solutions. The masculine media food is ‘festal’, dark, exclusive, time consuming and promotes unconcerned hedonism. However, the area of agricultural proficiencies seems to entail less unequivocal gender enactments that warrant closer inspection.